The Mediating Role of Street Code Attitudes on the Self-Control and Crime Relationship. Issue 10 (3rd October 2018) - Intravia, Jonathan; Gibbs, Benjamin R; Wolff, Kevin T; Paez, Rocio; Bernheimer, Allison; Piquero, Alex R
ABSTRACT: Research has demonstrated strong but independent attention to the role of self-control and street code attitudes in predicting criminal and violent behavior. Yet, there are good theoretical notions to believe that street code attitudes may be a salient mechanism in the self-control–offending relationship. Specifically, the present study investigates: (1) the extent to which self-control predicts adopting street code attitudes and (2) whether street code attitudes mediate the effect of self-control on criminal behavior. Using data collected from a multisite sample of over 900 young adults, we assess this mediation hypothesis for three distinct types of criminal activity: violent, property, and drug use. Our results reveal that individuals with lower self-control are more likely to adopt street code attitudes, that self-control is related to all three forms of offending, and that street code attitudes fully mediate the effect of self-control on violence, partially on property crime, but not in the case of drug use. Findings and directions for future research are discussed.